Small Bowel Obstruction - Aka, Allison A.; Wright, Jesse P.; DeBeche-Adams, Teresa (Clinics in Colon and Rectal Surgery, 2021)
Small bowel obstruction (SBO) remains a common problem for surgeons and nonsurgeons alike. Management of SBO has shifted from primarily being surgical to a nonoperative approach, which can be attributed to a multitude of reasons, including better understanding of the pathophysiology of SBO, the advent of laparoscopy, and improvement in diagnostic imaging. But given the nature of SBO, the need for surgical consultation continues to remain a necessity. This article will review the etiology, diagnosis, and management of SBO.
Keywords: small bowel obstruction; nasogastric tube; adhesive disease